Structural and functional characterization of a novel gene, Hc-daf-22, from the strongylid nematode Haemonchus contortus. Issue 1 (December 2016) - Guo, Xiaolu; Zhang, Hongli; Zheng, Xiuping; Zhou, Qianjin; Yang, Yi; Chen, Xueqiu; Du, Aifang
Abstract Background The strongylid nematodeHaemonchus contortus is a parasite of major concern for modern livestock husbandry because hostile environmental conditions may induce diapause in the early fourth-stage larvae. Methods A new geneHc -daf -22 was identified which is the homologue ofCe -daf -22 and human SCPx. Genome walking and RACE were performed to obtain the whole cDNA and genomic sequence of this gene. Using qRT-PCR with all developmental stages as templates to explore the transcription level and micro-injection was applied to confirm the promoter activity of the 5′-flanking region. Overexpression, rescue and RNA interference experiments were performed in N2, daf -22 mutant (ok 693 ) strains ofC. elegans to study the gene function ofHc -daf -22 . Results The full length gene ofHc -daf -22 (6, 939 bp) contained 16 exons separated by 15 introns, and encoded a cDNA of 1, 602 bp (533 amino acids, estimated at about 59.3 kDa) with a peak in L3 and L4 in transcriptional level. The Hc-DAF-22 protein was consisted of a 3-oxoacyl-CoA thiolase domain and a SCP2 domain and evolutionarily conserved. The 1, 548 bp fragment upstream of the 5′-flanking region was confirmed to have promoter activity compared with 5′-flanking region ofCe -daf -22 . The rescue experiment by micro-injection ofdaf -22 (ok693 ) mutant strain showed significant increase in body size and brood size in the rescued worms with significantly reduced or completely absent fat granules confirmed by Oil red O staining, indicating thatHc -daf -22 could partially rescue the function ofCe -daf -22 . Furthermore, RNAi withHc -daf -22 could partially silence the endogenousCe -daf -22 in N2 worms and mimic the phenotype ofdaf -22 (ok693 ) mutants. Conclusion The geneHc -daf -22 was isolated and its function identified usingC. elegans as a model organism. Our results indicate thatHc -daf -22 shared similar characteristics and function withCe -daf -22 and may play an important role in peroxisomal β-oxidation and the development inH. contortus .